Dᴇᴛᴇʀᴍɪɴᴇ ᴀ ʀᴇᴛᴀ ǫᴜᴇ ᴘᴀssᴀ ᴘᴇʟᴏs ᴘᴏɴᴛᴏs A=(0,-2) ᴇ B=(-4,0).​

Resposta :

Resposta:

[tex]\textsf{Leia abaixo}[/tex]

Explicação passo-a-passo:

[tex]\mathsf{m = \dfrac{\Delta_Y}{\Delta_X} = \dfrac{y_B - y_A}{x_B - x_A} = \dfrac{0 - (-2)}{-4 - 0} = \dfrac{0 + 2}{-4} = \dfrac{2}{-4} = -\dfrac{1}{2}}[/tex]

[tex]\mathsf{y - y_0 = m(x - x_0)}[/tex]

[tex]\mathsf{y - 0 = -\dfrac{1}{2}(x - (-4))}[/tex]

[tex]\mathsf{2y - 0 = -x - 4}[/tex]

[tex]\boxed{\boxed{\mathsf{y = \dfrac{-x - 4}{2}}}}\leftarrow\textsf{equa{\c c}{\~a}o reduzida}[/tex]

[tex]\boxed{\boxed{\mathsf{x + 2y + 4 = 0}}}\leftarrow\textsf{equa{\c c}{\~a}o geral}[/tex]